Understanding the Reflections of Battlefield Tourists Regarding Their Experiences to Sites Associated With WWI and the Vietnam War: An Analysis of Travel Blogs - Upton, Ann (Auckland University of Technology, 2015)
The travel and tourism industry is connected to the ideas of leisure and relaxation, however not all tourism sites and experiences occur in this way. Dark tourism or thanatourism relates to the darker side of travel; it has the potential to incite deeper feelings and emotions. It is commonly described as travel to places associated with death. For that reason battlefield tourism is a category of dark tourism. Battlefield tourism experiences have the potential to provoke the contemplation of life and death. The aim of this study is to explore online travel blogs to discover and understand the reflections of battlefield tourists who visit sites that have witnessed terrible loss of human life and acts of inhumanity, sites that represent the worst of humankind. This study takes an interpretivist approach, utilising qualitative and unobtrusive data collection methods to obtain relevant travel blogs. The selected case studies include sites associated with WWI (Belgium, France and Turkey) and sites connected to the Vietnam War (or American War), including the War Remnants Museum, Cu Chi Tunnels and My Lai. The selected research method involved the process of thematic analysis, which enabled the examination of 40 travel blogs, 20 blogs per case study. The rationale for these cases is that they have not been previously analysed in a study which focuses on the tourists’ reflections of their experiences at sites of historic warfare, and which focuses specifically on the concept of dark tourism and mortality. The findings suggest that tourists can have a deeply reflective experience at sites of historic warfare. In addition, they can also experience contested feelings towards the war narrative. The three key outcomes are: mortality mediation involving a connection with the dead, contemplation of their own mortality and viewing death statistics as real people. Another outcome was contested mortality mediation which occurred when tourists felt a dissonance towards the narrative of war. The third outcome was a connection with the living which included an emotional connection to the local people. These three outcomes led to the overall understanding of battlefield experiences, which is the meaning of life and humanity (connecting to people), and the passing of time (the writing of history – of winners and losers). The findings of this study add to the knowledge of battlefield tourism, helping to understand how tourists experience historic sites of war. With continued research there will come a greater understanding of how best to manage battlefield tourism sites and experiences in the present and future.
Keywords: Dark tourism; Battlefield tourism; WWI; Vietnam War; Mortality mediation; Tourist experience